The Nonlinear Magnetic Flux Diffusion in Superconductors - Begmuradov Shohzod Dilmurod O`Gli (Zien Journals, 2023)
The problem of the penetration of a magnetic field into a high-temperature superconductor, which is in the regime of flux creep in an external magnetic field, is considered. Analytical formulas are obtained for the depth and rate of penetration of a magnetic field into a superconductor depending on the values of the problem parameter, namely, on the exponent n characterizing the rate of penetration of vortices into the superconducting half-space.
Keywords: flow dynamics; magnetic induction; self-similarity